HLEYUVATSKA SUITE IN KRYVORIZHSKA STRUCTURE: PALEOGEOGRAPHIC FEATURES AND GENESIS OF METATERRIGENOUS DEPOSITS - Matischuk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paleogeography of Hleyuvatska suite is reconstructed based on the following techniques: comparison of weathering coefficients and aqueous differentiation suggested by O.O. Predovskyi; an ’ideal section’ method suggested by N.M. Strakhov, which means correlating indicator elements and depositional environment. Using V.K. Golovenka method and comparing Hleyuvatska suite chemistry with the average abundance of rock-forming oxides in magmatogene rocks, there is made an attempt to reconstruct climatic conditions of the suite’s deposition. Formation analysis made it possible to define probable sources of fragmentary material and ways of its transportation. By using the methods stated above it is revealed Hleyuvatska suite rocks to have been formed in the coastal marine conditions; marine pool sedimentation being shallow water with a low degree of salinity, a freshwater reservoir, actually. The comparison carried to approximate quantitative estimates of weathering and sedimentation intensity in meta-sedimentary strata of different paleotectonics relative to Hleyuvatska suite genesis and other techniques shows rocks to have been forming in conditions of moderate subsidence of the Kryvyi Rih structure. Climate is proved to be another factor to affect rock genesis. The use of different methods to reconstruct paleoclimatic conditions yielded diverse findings. Some methods show the rocks to have been formed in conditions of humid climate, while others in arid one. Relying on these data it can be assumed that the rocks were formed in the transition climatic conditions, from humid to arid, in fact. Sedimentary basin genesis resulted from an increase in tectonic activity within the affected area, as a result of which there was a dramatic lowering of the central part of the Kryvyi Rih structure. Sedimentations of clastic material came from two oppositely directed sources: the easternmost Saksahanskyi region in the south-east and West-Hanivskyi zones in the north-west.